Precision Analysis of Supraorbital Transcranial Exits Using Three Dimensional Multidetector Computed Tomography. Issue 6 (September 2019) - Lim, Nam Kyu; Kim, Young Ho; Kang, Dong Hee
Abstract : Purpose: Anatomical variation in supraorbital transcranial exits, which can be divided into the lateral supraorbital exit and the medial frontal exit, has been investigated in several studies during the past few decades. However, in previous studies, inconsistent criteria were used for classifying those exits. The authors analyzed variations in supraorbital transcranial exits using 3 dimensional multidetector computed tomography (3D MDCT), and present a consistent classification of the types of those exits with precise location measurements. Methods: In 1181 patients (2362 orbits) who underwent facial 3D MDCT, the authors measured a set of qualitative and quantitative parameters. The qualitative parameters included an assessment of the location and type of the exit, and the number of accessory foramina. The quantitative parameters included various distance measurements. Results: A frontal exit was present in 2071 orbits and a supraorbital exit in 953. Neither a frontal exit nor a supraorbital exit was found in 11 orbits. The most common type of frontal exit was the notch type, followed by the foramen type and none. The mean distance from the nasion to the frontal exit was 24.70 ± 3.50 mm on the right side and 23.69 ± 3.42 mm on the left side. Conclusion: In conclusion, various types of supraorbital transcranial exits were observed, of which the frontal notch was the most common. This is the first study to conduct a consistent analysis of a large sample of skulls to characterize the distribution of supraorbital transcranial exit types using a comprehensive and clear set of criteria. Abstract : Supplemental Digital Content is available in the text